Expansion and Fragmentation Internationalization, Political Change and the Transformation of the Nation-State - Kersbergen, van, Kees (Amsterdam University Press, 1999)
Is the end of the nation-state approaching, now that the international economy takes less and less notice of borders between countries and the European Union has already acquired so much political power? What does national autonomy mean when governments delegate any number of powers to international organizations? Internationalization leads to political change, and the position of the nation-state appears to be undergoing a radical process of erosion. The surprising conclusion of this book is that the political significance of the state will not be lost. The analyses show that both expansion and fragmentation of political power are characteristics of fundamental political change. While it is true that the state is delegating authority and that internationalization is limiting autonomy, the state is also finding new forms of cooperation and coordination, both nationally and internationally, to preserve and even to strengthen its power and autonomy. Contrary to widely held assumptions, the idea of a progressive weakening of the nationstate does not prove tenable.